Keanekaragaman Jenis Serangga di Berbagai Lahan Pertanian Kecamatan Basidondo - Putri, Adelia; Dhafir, Fatmah; Zainal, Syech; Sabran, Moh.; Agni, Raya; Sutrisnawati, Sutrisnawati (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to describe the level of diversity of insect species in various agricultural lands in Basidondo District, Tolitoli Regency, Central Sulawesi. The research was conducted in January-March 2025 using descriptive methods and quantitative approaches that aim to make a description or descriptive of a situation objectively using numbers. Insect sampling techniques were carried out with four types, namely pitfall trap, light trap, sweeping net, and hand collection. The insects obtained were then identified according to the taxonomic order with the help of insect determination key book, and analyzed using Shannon-Wiener diversity index (H'). The results showed that there were 24 types of insect families that were successfully identified. The value of the diversity index (H') was 3.13, which was classified as high diversity. These results indicate that agricultural land in Basidondo District has environmental conditions that support the diversity of insect communities, which can contribute to the stability of agricultural ecosystems. High diversity indicates a balance between insect pests and natural enemies, as well as the role of insects as pollinators and decomposers.